Branched‐chain ketoacids secreted by glioblastoma cells via MCT1 modulate macrophage phenotype - Silva, Lídia; Poschet, Gernot; Kneisel, Niclas; Seiffert, Martina; Hell, Rüdiger; Lichter, Peter; Radlwimmer, Bernhard (EMBO reports, 2017)
Elevated amino acid catabolism is common to many cancers. Here, we show that glioblastoma are excreting large amounts of branched‐chain ketoacids (BCKAs), metabolites of branched‐chain amino acid (BCAA) catabolism. We show that efflux of BCKAs, as well as pyruvate, is mediated by the monocarboxylate transporter 1 (MCT1) in glioblastoma. MCT1 locates in close proximity to BCKA‐generating branched‐chain amino acid transaminase 1, suggesting possible functional interaction of the proteins. Using in vitro models, we demonstrate that tumor‐excreted BCKAs can be taken up and re‐aminated to BCAAs by tumor‐associated macrophages. Furthermore, exposure to BCKAs reduced the phagocytic activity of macrophages. This study provides further evidence for the eminent role of BCAA catabolism in glioblastoma by demonstrating that tumor‐excreted BCKAs might have a direct role in tumor immune suppression. Our data further suggest that the anti‐proliferative effects of MCT1 knockdown observed by others might be related to the blocked excretion of BCKAs. Synopsis Glioblastoma cells excrete branched‐chain ketoacids (BCKAs) through the monocarboxylate transporter MCT1. BCKAs are taken up by macrophages and alter their metabolism and phagocytic capacity, possibly enhancing immune suppression in glioblastoma. Glioblastoma cell branched‐chain ketoacids are excreted via MCT1.Macrophages take up branched‐chain ketoacids.Branched‐chain ketoacids modulate macrophage metabolism and phagocytosis.